Proposed new interior design scheme of True Urban Park' beyond internet cafe' for True Corporation Bhd. at retail unit No. 3.2" Floor, Persiaran Medan Ipoh, 31400, Ipoh, Perak / Mohd Danial Hafiz Che Yaman - Che Yaman, Mohd Danial Hafiz (Faculty of Architecture, Planning and Surveying, 2011)
This thesis report is a manifestation of the student’s understandings and knowledge about the overall design aspects of interior design, from the early stages to the design proposal presentation stage. This thesis report is a report for a project entitled ‘Proposed New Interior Design Scheme of True Urban Park ‘beyond internet cafe’ for True Corporation Bhd. at Retail unit No. 3.2" Floor, Persiaran Medan Ipoh, Medan Ipoh, 31400 Ipoh Perak.’ The main purpose of this project is to born more competitive and spirited young Malaysian teenagers who love to compete among each other. This healthy competition is a good start of producing a more devoted and progressive youth community. It aims to promote a more organized lifestyle and provide the best qualities for the younger generation. True Urban Park is basically a place where youth of a higher class can spend time and do lots of fun activities together. However, the students must first go through all the steps and processes before continuing with the design process. Among the processes are identifying the client, completing site and building analysis, make a case study, and space planning. After completing all the processes, the students might start the design process based on the analysis and researches done previously. A good design should fulfill and satisfies the client’s requirements and at the same time attractive and practical in order to attract more customers, and ease the client’s operational and management system.